INFORMED CONSENT IN ADVANCE CARE PLANNING IN THE PALLIATIVE CARE SETTING: A DECISION AID LIBRARY FOR END OF LIFE CARE. Issue 2 (1st June 2013) - Krones, T; Loupatatzis, B; Steffen-Bürgli, B; Otto, D; Brunner, M; Biller-Andorno, N; Eisele, G; in der Schmitten, J; Mitchell, C; Obrist, S; Poster, D; Rordorf, T; et al.
Abstract : Background: Advance care planning has been discussed from a variety of perspectives. It aims to support a patient-centred process in which patients, together with their loved ones and their caregivers, are enabled to make informed decisions regarding future health care events. Although both accurate information about prospective health care problems and alternatives and help with personal decision making by advance care planning facilitators are crucial, the information given to patients in an ACP process is mostly rough, short, and left to physicians and thus does not fulfil the criteria of an 'evidence based patient choice' nor even of general standards for "informed consent" Aim: To construct an evidence based paper and video-based Decision Aid Library for End of Life Care for best patient information supporting the ACP facilitation process Methods: We screened the literature for evidence-based information and evidence-based decision aids regarding (1) general Goals of Care, (2) Resuscitation (3) Tube Feeding (4) Antibiotics, (5) Ventilation (6) Dialysis Withdrawal and (7) last place of Care and constructed a library of evidence-based decision aids, qualitatively pretested by staff and patients. Results: Following a methodical screening process, a library of evidence-based papers and videos was constructed, which is currently being qualitatively evaluated by staff and patients as the first step in a grant-funded randomised controlled trial on the effect on ACP for palliative care patients in Switzerland. Discussion: We will discuss the content and qualitative results of the Decision Aid Library at the Melbourne Conference Conclusion: From an ethical point of view, best information is crucial for making informed choices. If the decision aid library proves to be useful, evidence-based information and decisions aids should become part of ACP programmes.